Komunikasi Politik Sultanah Safiatuddin Aceh - Muarrief Rahmat (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2022)
The leadership of Sultanah Sri Ratu Safiatuddin has given birth to new values related to the presence of women in the power of the Kingdom of Aceh Darussalam. Through his policies, he has contributed greatly to a new perspective in the political history of Aceh. His collaborative policies have provided opportunities for everyone to be involved in the Aceh Darussalam government system regardless of background, especially gender. This paper attempts to unravel and analyze Ratu Safiatuddin's pattern of political communication regarding his policies that led to the trust of the Acehnese people at that time to be led. Among them include policies in the field of science and knowledge, strengthening the law, freedom of opinion, and gender equality. The results of this study show that through this policy the Queen can survive in a span of 35 years and even continues with three queens' leadership in the next period. Ratu has contributed new ideas for the fulfillment of the value of the existence of Islam and science.